Tourism and Global Environmental Change - Gössling, Stefan; Hall, Michael C. (Contemporary Geographies of Leisure, Tourism and Mobility, 2006)
This fascinating book is the first comprehensive analysis of the economic, social and political interrelationships between tourism and global environmental change: one of the most significant issues facing humankind today. Its contributors argue that the impacts of these changes are potentially extremely serious both for the tourism industry, and for the communities dependent upon it. Integrating knowledge from the social and physical sciences, this significant book explores they key issues surrounding global environmental change, as well as government and industry willingness to meet the challenges posed by it. Divided into four main sections, it investigates: the tourism and global environmental change relationship in specific environments global issues related to environmental change differing perceptions of global environmental change held by tourists and the tourist industry. Comprehensive in scope, topical and integrative, this key text is essential reading for students, scholars and researchers in all aspects of tourism, geography and environmental studies.